The spectrum of B cells in the pathogenesis, diagnosis and therapeutic applications of immunoglobulin G4‐related disease - Qiyuan Hao; Meng Sun; Yanying Liu (Clinical & Translational Immunology, 2023)
Abstract Immunoglobulin G4 (IgG4)‐related disease is a chronic fibroinflammatory disease mediated by immune disorders. Given the challenging clinical diagnosis and treatment, knowledge of the pathogenesis of IgG4‐related disease is important. The typical elevation of serum IgG4 concentrations and infiltration of IgG4‐positive plasma cells in the involved tissues indicate the involvement of B lymphocytes in the pathogenesis of IgG4‐related disease. Mass production of autoantibodies reflects abnormal activation of B cells, which causes tissue damage. Circulating plasmablasts are recently discovered markers that correlate with serum IgG4 concentration, the extent of organ involvement and disease activity. B‐cell depletion therapy is an emerging curative strategy that can significantly alleviate clinical manifestations and achieve remission in patients with IgG4‐related disease. These findings highlight the potential role of B cells in IgG4‐related disease. In this review, we discuss the pathogenic impact of B lymphocytes on IgG4‐related disease and describe novel therapies targeting B cells.